Description of Facilities and Forms of Professional Teaching at Higher School as Constituents of the Pedagogical System - Viktoriya Bilyk (Pedagogical Discourse, 2013)
The essence of term pedagogical system and its components are considered. The description of facilities and forms of professional teaching of the future specialists at higher school, as components of the pedagogical system is given. The classification of forms of teaching and the modern organizational forms of teaching are considered. The advantages of introduction of the concentrated teaching are argued. The question of using the facilities of teaching at higher school is reflected. The attention on computer facilities of teaching is accented. The necessity of the complex using of facilities of teaching in professional preparation of the  future specialists is marked.